Little evidence of systemic and adipose tissue inflammation in overweight individuals - Redman, Leanne M.; Tam, Charmaine S.; Covington, Jeffrey D.; Ravussin, Eric (Frontiers in Genetics, 2012)
Context. The effect of weight loss by diet alone or diet in conjunction with exercise on low grade inflammation in non-obese (overweight) individuals is not known. Objective. Test the hypothesis that 24 weeks of moderate CR (25%) by diet only or with aerobic exercise would reduce markers of systemic inflammation and attenuate inflammation gene expression in subcutaneous adipose tissue. Design. Randomized controlled trial. Setting: Institutional Research Center. Participants. Thirty-five overweight (BMI:27.8±0.7kg/m2) but otherwise healthy participants (16M/19F) completed the study. Intervention. Participants were randomized to either calorie restriction (CR: 25% reduction in energy intake, n=12), caloric restriction+exercise (CR+EX: 12.5% reduction in energy intake+12.5% increase in exercise energy expenditure, n=12) or control (healthy weight-maintenance diet, n=11) for 6 months. Main outcome measures. Fasting serum markers of inflammation (Leptin, hsCRP, IL-6, TNF-α) and inflammation-related genes (CD68, IL-6, TNF-α, MIF, MCP-1, Adiponectin, PAI-1) in subcutaneous adipose tissue. Results. CR and CR+EX lost similar amounts of body weight (-10±1%), fat mass (-24±3%), visceral fat (-27±3%) and had increased insulin sensitivity (CR:40±20%, CR+EX:66±22%). Leptin was significantly decreased from baseline (P<0.001) in both groups however TNF-α and IL-6 were not changed. hsCRP was decreased in CR+EX. There was no change in the expression of genes involved in macrophage infiltration (CD68, MIF, MCP-1, PAI-1) or inflammation (IL-6, TNF-, adiponectin) in either CR or CR+EX. Conclusion. A 10% weight loss with a 25% CR diet alone or with exercise did not impact markers of systemic inflammation or the expression of inflammation-related adipose genes in overweight individuals.